Fintech dan Literasi Keuangan Syariah di Kalangan Mahasiswa: Peran Modal Sosial Islam dalam Mempromosikan Inklusi Keuangan Islam - Amalia, Bella (Journal of Islamic Economics (JoIE), 2025)
Introduction: This study examines the influence of Islamic financial literacy and financial technology on Islamic financial inclusion, with Islamic social capital as a mediating variable a novel approach rarely explored. Despite the rapid growth of the Islamic finance industry, literacy and inclusion remain low, particularly among the youth. By focusing on Islamic economics students at the University of Jember, this research offers contextual insights and highlights its novelty by integrating cognitive, technological, and Islamic social value dimensions to support digital-based financial inclusion. Research Methods: Using a quantitative, explanatory approach, the research focuses on 378 students selected via purposive sampling. Primary data was collected and analyzed using Variance-based SEM (Partial Least Square) with WarpPLS 8.0. Results: The findings reveal that Islamic financial literacy and financial technology both significantly influence Islamic social capital, each with a significance value of <0.001. Moreover, both Islamic financial literacy and financial technology significantly affect Islamic financial inclusion, directly and through Islamic social capital, with all significance values being <0.001. The Islamic social capital itself has a significant positive effect on Islamic financial inclusion. Conclusion: The coefficient of determination (R²) for the model stands at 52% and 74%, indicating a strong explanatory power for the variations in Islamic social capital and financial inclusion among the students.